A Narrative Review of Risk Factors for Postoperative Complications in Neonates: Integrating Patient, Surgical, and Anesthetic Determinants for Optimized Perioperative Care - Pan Jiang (Asploro Journal of Biomedical and Clinical Case Reports, 2026)
Objective: To review the main risk factors for postoperative complications in neonates and provide references for optimizing perioperative management. Methods: Literature published between 2000 and 2024 in databases such as PubMed was retrieved. Patient-, surgical-, and anesthesia-related risk factors for postoperative complications in neonates were summarized and analyzed. Results: The occurrence of postoperative complications in neonates is the result of multiple factors. Patient factors, such as prematurity, low birth weight, and severe comorbidities; surgical factors, such as emergency surgery and operation duration; and anesthesia- and perioperative management-related factors, such as preoperative status and intraoperative hemodynamic fluctuations, are all key elements affecting prognosis. Conclusion: Identifying and evaluating high-risk factors and performing preoperative optimization and refined intraoperative management through multidisciplinary collaboration are important strategies to reduce the incidence of postoperative complications in neonates and improve their surgical outcomes.